(3OjhGf GHf NGJeIs - (3CMeO Hf Ydj Hf eMeO Hf NGJeI GdCfUGQj, CHhLYaQs
(3ChdgG (B:s
(3hHYO(B: (3aEf HYV NdUGFj, hgh eef dG jSY HLejd hOg ZjQ Jcejd aVdg, NWH Edqj ef HfGJ acQj CHjGJ TYQj LedI jSgd ESJXgGQgG s
(3BNQgG (B:s
(3aXddJ CHcj HCSqF hMfjf dj OehY ZRGQ fWbJ jhe SGQhG HSQi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B286 - (3U(B397s
(3cGf GdeDda MjkG SfI (B770(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B19s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B94 s
Keywords: (3GdCOHs